(untitled) (Research, Society and Development, 2019)
This article exposes the important trajectory of the Captain State School of Penha in the interior of Rio Grande do Norte. In this study, the objective is to know its history and its influence, based on the empirical data collected through the narratives of people involved, which served as a basis for understanding this space as a sociocultural focus of the Earth of Abalos, the name used to refer to the municipality of João Câmara, located in the Brazilian interior of Rio Grande do Norte. Our methodology is characterized by a qualitative research of (auto) biographical content, using technical procedures that are based on a testimonial source (autobiographical report), documentary (bibliographic research) for the construction of a System of Theoretical- Conceptual Reference (GONZÁLEZ, 2017), in documents and empirical. The collected information was examined with the analytical strategy of Immersion and Hermeneutic Contemplation (GONZÁLEZ, VILLEGAS, 2009), in order to understand the socio-cultural influences of Terra dos Abalos by Zé da Penha. Rescuing from the historicity of the State School Captain José da Penha, which has been lost over the years and needs to emerge, since the citizens do not hold the knowledge about the history and foundation of the city where they live.